SAUNG BACA DAN BELAJAR BERSAMA MEMBUKA WAWASAN ILMU PENGETAHUAN MELALUI LITERASI MEMBACA DAN BELAJAR - Susan Nindi Desiani (Swadaya: Indonesian Journal of Community Empowerment, 2021)
Abstract In terms of education, there are currently many shortcomings in terms of learning, especially for face-to-face learning by switching the learning system from face-to-face to online learning so that children tend to be increasingly difficult to adapt in understanding learning materials due to restrictions on the learning system and the lack of media to support online learning. . Therefore, seeing the Covid-19 pandemic situation that affects the learning system, we propose to establish a Reading Saung. Saung Baca is one of the activities of the Student Work Lecture program and the College of Pharmacy in the village of Ciledug Lor. This activity is intended for the Ciledug Lor community, especially children who are less able to understand learning at school. Seeing the situation during the Covid-19 Pandemic, which is increasing day by day and affecting the learning system, therefore to improve the learning system, the Saung Baca activity should be carried out which aims to open up scientific knowledge through reading and learning literacy so that children can learn and understand lessons. although the learning that is done at school is not face-to-face. This reading room is held every afternoon at 16.00 WIB which is attended by the community, especially kindergarten, elementary and junior high school children, which aims to help children to be able to learn optimally. Keywords: reading room, student work lectures, community empowerment, reading literacy